The influence of interstitial cells of Cajal density in the outcomes of pyeloplasty in adults: A prospective analysis. Issue 1 (February 2023) - Srougi, Victor; Bandeira, Rodolfo Anisio Santana de Torres; Reis, Sabrina Thalita; dos Santos, Gabriel Arantes; Andrade, Hiury da Silva; Leite, Katia Ramos Moreira; Hamilton-Cho, David; Mitre, Anuar Ibrahim; Arap, Marco Antonio; Srougi, Miguel; Duarte, Ricardo Jordão
Purpose: To evaluate if the density of interstitial cells of Cajal (ICC) in the ureteropelvic junction (UPJ) influences the outcomes of pyeloplasty in adults. Methods: Twenty-three patients with the diagnosis of ureteropelvic junction obstruction (UPJO) that underwent laparoscopic dismembered pyeloplasty were included. ICC density was measured using immunohistochemistry reaction for c-KIT expression in the resected UPJ segment. Pyeloplasty outcome was evaluated by patient self-report pain, urinary outflow using DTPA renogram and hydronephrosis assessment using ultrasound (US) at 12 months of follow-up. A logistic regression analysis was performed to assess the association of pyeloplasty outcomes and ICC density. Results: Low, moderate, and high ICC density were present in 17.4%, 30.4%, and 52.2% of the patients, respectively. Complete pain resolution was observed in 100%, 85.7%, and 75% of patients with low, moderate and high ICC density, respectively ( p  = 0.791). DTPA renogram improved in 75%, 85.7%, and 91.7% of patients with low, moderate and high ICC density, respectively ( p  = 0.739). Hydronephrosis improved in 25%, 85.7%, and 91.7% of patients with low, moderate and high ICC density, respectively ( p  = 0.032). Conclusions: Patients with high ICC density have a significant amelioration of hydronephrosis after pyeloplasty. However, ICC density is not associated with functional outcomes.